Reverse vaccinology-based multi-epitope COVID-19 vaccine targeting SARS-CoV-2 structural and non-structural proteins induces immune responses in mice - Azzania Fibriani; Nicholas Yamahoki; Annisa Meliana Shani; Afifatur Rofiqoh; Agust Leo Fany Siregar; Cynthia Gunawan; Carola Giovanni Danira Mayorga; Tommy Octavianus Soetrisno Tjia; Husna Nugrahapraja; Ernawati Arifin Giri-Rachman; Marselina Irasonia Tan (Vaccine: X)
Vaccination is effective to end pandemics, including the Coronavirus disease-2019 (COVID-19). However, the evolution of Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) which is characterized by the emergence of the virus variants has a great potential to cause a decrease in the effectiveness of the developed vaccines. One of the vaccine platforms that may overcome vaccine failure due to viral genetic mutations is a multi-epitope vaccine. Using the reverse vaccinology approach, in this study, we developed a multi-epitope peptide-based COVID-19 vaccine composed of immunodominant epitopes. The multi-epitope peptide was designed in silico, successfully expressed in E. coli BL21 (DE3), and purified. Furthermore, the vaccine candidate was proven to induce the production of SARS-CoV-2 antigen-specific IgM and IgG antibodies in BALB/c mice without any considerable adverse reaction. The results also showed that the generated antibodies were reactive to SARS-CoV-2-positive patient nasopharyngeal swab samples containing different circulating Omicron XBB F456L variants. Therefore, our study demonstrates that the multi-epitope peptide has the potential to be further developed as a safe and relevant COVID-19 vaccine. Additionally, this study also demonstrates that reverse vaccinology is useful to facilitate the development of relevant vaccines for emerging infectious diseases.